Effects of tree-length timber skidding on soil compaction in the skid trail in Hyrcanian forests - Jourgholami, Meghdad; Majnounain, Baris; Etehadi Abari, Maryam (Forest Systems, 2014)
Aim of study: The study was conducted to examine impact of skidding traffic, trail slope, traffic frequency, and soil depth on the soil bulk density.Area of study: This study was carried out in the Kheyrud Forest in Hyrcanian forest, Iran.Material and methods: The level of soil compaction at eight levels of traffic (1, 4, 8, 10, 15, 20, 25, and 30 passes), four levels of skid trail slopes (0, 10, -10, and -20%) and three soil depth (5, 15, 25 cm) were applied in three replicates consequently. Bulk densities were measured on the undisturbed surface (control) and within the tracks. Timbers were extracted in the tree-length logging method using rubber-tired skidder (Timberjack 450 C).Main results: About 5.2% of total area of harvesting unit were disturbed and compacted. Uphill skidding increases compaction more than downhill skidding. In the four different slopes, the highest increasing of the bulk density was occurred during the first few passes of skidder, although the bulk density continued to increase in amount and depth with the number of passes. The increases in bulk density were still important at the maximum sampling depth of 20-30 cm.Research highlights: The results indicated that slope steepness had a strong effect on the soil physical properties and soil disturbance. Designated skid trails should be used to minimize the influence on the forest soil.Key words: soil compaction; tree-length logging method; rubber-tired skidder; Hyrcanian forest.